Magnitude and features of methanol poisoning. Hospital Nacional Dos de Mayo - Contreras Camarena, Carlos (2019)
Objective: To determine the magnitude, and clinical and biochemical features of methanol poisoning in patients admitted to the emergency room of the Hospital Nacional Dos de Mayo. Materials and methods: An analytical study was performed with data from patients diagnosed with methanol poisoning who were admitted to the emergency room of the Hospital Nacional Dos de Mayo, Lima, Peru. Collected data included age, gender, occupation, place of origin, cocaine use, chronic alcoholism, HIV infection, and clinical data associated with methanol poisoning. For the analysis, statistical measures of central tendency and dispersion were used, and 2x2 contingency tables were developed in the bivariate analysis. For the evaluation of the likelihood ratio, confidence intervals were established at 95 %, and a p-value < 0.05 was considered significant. Results: Ninety percent (90%) of the cases occurred due to the accidental ingestion of an adulterated drink. Eightyseven point five percent (87.5 %) of the patients had low socioeconomic status. Average blood methanol level was 72.04 mg/L (SD ± 39.70) and overall mortality was 12.5 %. The predominant biochemical profile was severe high-anion gap metabolic acidosis. Conclusions: Methanol poisoning accounts for 0.15 % of total emergency room consultations. Its clinical profile is characterized by hypotension, tachycardia, tachypnea, sensory disorders, vomiting, mydriasis and nystagmus. Severe metabolic acidosis was associated with increased morbidity and mortality.